Crack deflection and interfacial fracture energies in alumina/SiC and alumina/TiN nanocomposites - Jiao, S; Jenkins, M (1997)
Crack/particle interactions in Al2O3/SiC and Al2O3/TiN nanocomposites have been observed by TEM on samples containing cracks produced by Vickers indentations. No significant crack deflection by intragranular SiC particles or microcracking around nanoparticles was found. Intergranular cracks were observed to be deflected into the matrix grains by SiC particles on grain boundaries inclined to the direction of crack propagation. TiM particles were not effective in this way. These features are briefly discussed within the framework of the interfacial fracture energies. These were calculated from interfacial energies, which were determined by the measurement of grain boundary-interface dihedral angles.